Consumer Goods: Pengaruh Profitabilitas dan Leverage Terhadap Nilai Perusahaan Dimediasi oleh Corporate Social Responsibility - Munzir Munzir; Yoga Andriyan; Rahmat Hidayat (Jurnal Akuntansi dan Governance, 2023)
This study aims to analyze the effect of profitability and leverage on corporate value with the moderating role of CSR. This study employs a quantitative approach with secondary data. The population is a consumer goods company listed on the Indonesia Stock Exchange. With purposive sampling, 87 sample companies were selected. This study uses path data analysis. The results show that profitability has a negative and significant effect on CSR disclosure, while leverage has a negative and insignificant effect on CSR disclosure. Profitability has a positive and significant effect on corporate value, leverage has an insignificant positive effect on firm value, and CSR has a significant negative effect on corporate value. Finally, CSR disclosure is not able to mediate the influence of profitability and leverage on corporate value